Value Relevance of IFRS 7 Financial Instruments Disclosures for Listed Insurance Firms in Nigeria - Olawale Nurudeen, Sanni; Olajide David, Dahunsi; Ayodele Samson, Adesina (International Journal of Economics, Management and Accounting, 2022)
The change in accounting regulations is as a result of the weaknesses of Nigeria General Accepted Accounting Principles (GAAP) and low disclosure requirements. International Financial Reporting Standard (IFRS) reporting has more disclosures than Nigeria GAAP especially for financial institutions. Under Nigeria GAAP financial instruments have not been classified as in IFRS. This study therefore examined value relevance of IFRS 7 financial instruments disclosures for listed insurance firms in Nigeria from 2012 to 2018. The study used census sampling technique to arrive at fifteen (15) out of 27 listed Insurance firms for the period 2012 to 2018. It was arrived at on the premise that the firms have been complying with the IFRS 7 requirements for seven years. Quasi experimental research was adopted. Agency theory and signalling theory were used to underpin the study. The study used the Ohlson Model (1995) to establish to what extent firm accounting information influences share price valuation. Pooled robust OLS was used to analyze the data extracted from published annual financial reports of studied listed insurance firms in Nigeria. Comparatively, evidence obtained shows that book value is positively and statistically more value relevant than earnings per share in the second and the third models. In line with the findings, therefore, we recommend that regulators in the Financial Reporting Council of Nigeria (FRCN) enforce adequate measures on behavioural reporting of insurance firms to enhance financial information quality and increase value relevance.